Lemahnya Pengawasan Pemerintah terhadap Penebangan Hutan sebagai Penyebab Banjir di Sumatera Ditinjau dari Hukum Administrasi Negara - Dinda Amalia Nst; Anisa Amelia Purba; Ayu Tri Cahyani; Josua Armando Tamba; Reylan Silversius Sinaga; Robintang Lumbanbatu; Rohana Manalu; Taufiq Ramadhan (Universitas 17 Agustus 1945 Semarang, 2026)
This study looks at how the government isn't doing enough to watch over logging in Sumatra and how that leads to a higher chance of flooding, using the ideas from Administrative Law. Ineffective supervision, both during the licensing process and afterwards, significantly contributes to the decline of the forest's ecological functions, resulting in hydrological disasters. The study uses normative law and follows a literature review method. The data used consists of secondary data, including primary legal materials such as legislation, as well as secondary materials like textbooks, academic journals, and digital sources. Data was gathered by looking at documents and then looked at using a descriptive-qualitative approach. The research shows that the government's failure to properly carry out its responsibilities in forestry management can be considered an illegal government action, known as an 'onrechtmatige overheidsdaad'. This action goes against the General Principles of Good Governance (AUPB), especially the principles of being careful with public money, being responsible, and ensuring that laws are clear and followable. This situation leads to the government being responsible, which means they must take steps to fix the environment and offer help to the communities that were affected. This study suggests strengthening the forestry oversight system by implementing regulatory improvements, improving the capacity of officials, utilizing technology, and involving the community actively to ensure transparent, accountable, and sustainable environmental management.